Perspectives and practices on time out as a discipline method of selected preschool teachers - Jaraula, Constance Marie B.
Presented in this paper are the perspectives and practices of time out as a discipline method of selected preschool teachers in Cagayan de Oro City. In terms of the preschool teachers' perspectives, what are described are their behaviors, ides, beliefs and assumptions on time out. These perspectives deal mostly with how the teachers perceive time out to be and their assumptions on the factors that influence the us of time out as a discipline method. In regards to time out practice, focus is made oh how the selected preschool teachers implement the time out method in their classrooms. Five nursery teachers were randomly selected from among the other nursery teachers who teach in schools located within the city proper of Cagayan de Oro. Data presented for the perspectives are based on the interviews with the teachers, questionnaire and profile form given to the teachers. Open-ended questions were asked for the 3 interview schedules. First interview was conducted before the researcher started observing a subject's class. Second interview was conducted after the 5th observation day and a teacher profile form were given to the teachers at the end of the 3rd interview. The researcher also observed each teacher for 10 days and made a transcript of records based on what transpired during during 10-day observation. This transcript became the basis for the data presentation of the teacher' practice on time out as a discipline method. Results of this study showed that two teachers perceive time out as an immediate solution to behavioral problem. Three teachers perceive time out as a needed break away from an emotional and stressful solution. The same two teachers consider the factor when a child does not follow agreed upon rules as influential in the use of time-out. The same three teachers consider the factor when a child disrupts an on-going activity as a factor influential in the use of time out as a discipline method. Other factors common to the five teachers are the age of the child and time out location. Findings of this paper suggested that the teachers' implementation of the time out method does not approximate the steps involved in the Time out series of Jan Wilson. This due to the teachers' limited background and lack of sound knowledge on what time out is and how it should be implemented. Proper exposure by means of seminar attendance, sufficient background on child education by means of regularly updating one's working knowledge, and support from the school administration.